EARLY CHILDHOOD EDUCATION PRACTICES IN ZANZIBAR: PARENT’S INVOLVEMENT IN THE LEARNING OF THEIR CHILDREN IN PRE-PRIMARY EDUCATION - Chai, Ali; Renatus , Mligo; Shaghembe , Nsolezi (African Journal of Education and Practice, 2022)
Purpose: The purpose of this study was to explore parent's involvement in the learning of their children in pre-primary education (PPE). Parent's involvement has a wide sense in modern education trends, evolving parent's lifelong participation in children's school activities. In this regard, it would be difficult to cover the topic in this wide sense. Therefore, the study was more focused on exploring the ways that parent's get involved in the learning of their children in PPE, identify the challenges for low parent's involvement and suggest strategies to improve parent's involvement in the learning of their children in PPE. Methodology: The study employed qualitative methodology and a case study design where only PPE level among other levels of education was involved. A total number of 24 participants were participated in the study where by 10 were parents and 14 were pre-primary school teachers. The study was guided by the Ecological System Theory. Data was generated by using semi structured interviews and focus group discussion guided by a series of open ended questions as well as documentary review. Findings: The study reveals that parents were involved in parenting, school meeting and in helping their children's academic works. Shortage of time, parent's illiteracy, poor school experience of parents and the lack of sensitive learning programs between school and home limited parents to get involved in the study of their children. Also, the study found that creating effective communication between school and home, developing guidelines for parental involvement as well as creating collaborating academic activities between school and home were the strategies to improve parent's involvement in the study of their children in PPE. Unique Contribution to Theory, Practice and Policy: The study recommends that PPE schools should create conducive atmosphere for mutual contact between teachers and parents so as to enable parents to visit the school and contact with teachers regularly for their children's learning progress. Also, policy makers should integrate PPE with parenting styles so as to raise awareness and equip parents with knowledge on the vital role of participating in the education of their children.